2014
DOI: 10.1539/joh.14-0118-oa
|View full text |Cite
|
Sign up to set email alerts
|

Work Stressors, Perseverative Cognition and Objective Sleep Quality: A Longitudinal Study among Dutch Helicopter Emergency Medical Service (HEMS) Pilots

Abstract: Work Stressors, Perseverative Cognition and Objective Sleep Quality: A Longitudinal Study among Dutch Helicopter Emergency Medical Service (HEMS) Pilots: Mirjam RADSTAAK, et al. Behavioural Science Institute, Radboud University Nijmegen, The Netherlands— Objectives This longitudinal study examined the associations between work stressors, perseverative cognition and subjective and objective sleep quality. We hypothesized work stressors to be associated with (i) poor nocturnal sleep quality and (ii) higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…This result strengthens the assumption that work stressors may lead to an incomplete recovery, even during periods of rest from work such as those on Sundays. During Sunday, psychophysiological activation may be sustained even when workers are no longer exposed to any job demand or stressor, for example, due to perseverative cognitions, as shown recently by a study on helicopter pilots (Radstaak et al 2014). Future studies should compare the relationship between social stressors at work and recovery on non-working Sundays both with preceding working Saturdays and also with preceding work-free Saturdays.…”
Section: Discussionmentioning
confidence: 87%
“…This result strengthens the assumption that work stressors may lead to an incomplete recovery, even during periods of rest from work such as those on Sundays. During Sunday, psychophysiological activation may be sustained even when workers are no longer exposed to any job demand or stressor, for example, due to perseverative cognitions, as shown recently by a study on helicopter pilots (Radstaak et al 2014). Future studies should compare the relationship between social stressors at work and recovery on non-working Sundays both with preceding working Saturdays and also with preceding work-free Saturdays.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, lower HF-HRV has also been associated with greater emotional arousal in response to stress [22]. Poorer emotion regulation during stressful times is often translated into higher emotional and cognitive arousal at bedtime, which, in turn, is related to poorer sleep [70,71]. Impaired physiological, emotional, and cognitive arousal regulation thus represents potential pathways through which low HF-HRV might increase vulnerability to stress-related sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…We find the recent publication a satisfying reparation. Many studies have shown that excessive worrying can increase the risk of illness in the long term (Broadbent, Petrie, Alley, & Booth, 2003; Brosschot & van der Doef, 2006; Fortune et al, 2003; Gerin et al, 2012; Holman et al, 2008; Jellesma, Verkuil, & Brosschot, 2009; Radstaak, Geurts, Beckers, Brosschot, & Kompier, 2014; Thayer. & Brosschot, 2010; Tully, Cosh, & Baune, 2013; Van Laethem et al, 2015; Verhoeven et al, 2009; Verkuil et al, 2011; Verkuil & Brosschot, 2016; Verkuil, Brosschot, Gebhardt, & Korrelboom, 2015; Verkuil, Brosschot, Gebhardt, & Thayer, 2010; Verkuil, Brosschot, Meerman, & Thayer, 2012).…”
Section: Perseverative Cognitionmentioning
confidence: 99%